Peran Pondok Pesantren Madinatul Ilmi Dalam Pelaksanaan Dakwah Di Desa Kotarindau - Aldiawan Aldiawan (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2022)
This study aims to describe the role of the madinatul ilmi dolo Islamic boarding school in the implementation of da'wah in the Kotarindau village, Dolo sub-district, Sigi district through religious activities involving the local community. The author collects data through literature review, field observations and interviews with the leaders and supervisors of the madinatul ilmi dolo Islamic boarding school as well as several local community leaders. After conducting the research, the findings are formulated as follows: the role of the madinatul ilmi Islamic boarding school in carrying out its da'wah, namely First; held intensive Islamic studies once a month which was attended by the people of the Kotarindau village. Second; provide guidance on reading and writing the Qur'an. Third; open opportunities for the people of the Kotarindau village to participate in education at the Madinatul Ilmi Dolo Islamic boarding school. Fourth ; Every month of Ramadan, the Madinatul Ilmi Islamic Boarding School always holds a flash boarding school that examines several yellow books and is open to the public